عوارض الأهلية وأثرها في عقود التبرعات على ضوء قانون الأسرة الجزائري - معمري, إيمان (Universty of Eloued جامعة الشهيد حمه لخضر, 2021)
الملخص: يتناول هذا الموضوع بالبحث أحكام الأهلية وعوارضها والنظام القانوني لعقود التبرعات "الهبة، الوصية، الوقف" في قانون الأسرة الجزائري، وبيان أثر عوارض الأهلية عليها. وبالتالي الخروج بأحكام توضح مقتضياته. لذلك فقد تم التطرق فيه إلى تبيان حقيقة عوارض الأهلية وأنواعها المختلفة، بالرجوع إلى القانون المدني، سواء تلك التي تنقص أو تعدم الأهلية وأثرها على عقود التبرعات، وأيضا الوصول للاختلاف فيها ما بين الشريعة الإسلامية وقانون الأسرة الجزائري. بالإضافة إلى تحديد مدى مسؤولية المصاب بعارض من عوارض الأهلية في إبرام عقود التبرعات، وختم البحث بالتطرق إلى الآليات القانونية التي اعتمدها المشرع الجزائري لحماية ناقصي وعديمي الأهلية في التصرفات الواردة على عقود التبرعات. Résumé : فرنسية أو انجلزية This topic examines the provisions and symptoms of eligibility and the legal system for donations contracts "Gift, Testament, Endowment (Wakf)" in Algerian family law, and to show the impact of the eligibility symptoms on them. Thus, there are provisions that clarify its requirements. Therefore, it was addressed in the reality of the symptoms of eligibility and its various types, referring to the Civil law, Whether those lack or disqualify eligibility and their impact on donations contracts, as well as the difference between Islamic law and Algerian family law. In addition to determining the extent of responsibility of the victim of a symptom of eligibility in the conclusion of donations contracts, The research concluded by addressing the legal mechanisms adopted by the Algerian legislator to protect the imperfect and the incompetent in the conduct of the donation contracts.
أطروحة دكتوراه تخصص القانون الخاص في العلوم السياسية قسم الحقوق
Keywords: أهلية؛ عوارض؛ عقود؛ تبرعات؛ حماية؛ أثر؛ انعدام؛ نقصان؛ وقف؛ وصية؛ هبة؛ إبرام؛ حجر؛ قوامة؛ نيابة شرعية؛ مسؤولية.; Eligibility, Symptoms, Contracts, Donation, Protection , impact, Deprivation, lack, Endowment (Wakf), Testament, Gift , Create, Interdiction, Trusteeship, Legitimate Prosecution, Liability